Primary School Teachers’ Understanding of Critical Thinking in KSSR Classroom and Its Importance to Students - Wirawani Kamarulzaman (2018)
To investigate the primary school teachers’ understanding of critical thinking skills in KSSR classroom. To explore teachers’ perception on the importance of critical thinking to students